Electrophoretic deposition of graphene-based materials and their energy-related applications - Diba, Mani; Boccaccini, Aldo R. (CRC Press, 2016)
Electrophoretic deposition (EPD) is an attractive technique for the controlled manipulation and deposition of nanoscale materials. This solution-based technique is cost effective and requires simple equipment, providing several advantages for the processing of nanostructured coatings, including size scalability, dense packing, and site selectivity of the deposition. A precondition for the EPD processing of materials is their ability to form stable suspensions with adequate surface charge of the suspended (nano) particles. For the last few years, EPD has been increasingly considered for the processing of graphene-based materials. While pristine graphene can be modified to form stable suspensions, graphene oxide (GO) can be easily dispersed in stable aqueous suspensions due to the presence of polar functional groups in its structure leading to its high hydrophilicity. Moreover, after EPD, GO can be reduced via different routes to achieve partial restoration of pristine graphene properties. Not only has EPD shown promising results for deposition of graphene family materials, but it can also be utilized to produce graphene-based composite films or coatings at ambient conditions and without using any potentially hazardous chemicals. This chapter provides an overview of the EPD processing of graphene family materials, discussing the fundamentals and challenges involved in this process, describing also the energy-related applications of EPD-prepared graphene/GO films and coatings.
CRIS-Team Scopus Importer:2022-08-05